NEW SPECIES OF LATE EOCENE DERMESTID BEETLES (COLEOPTERA, DERMESTIDAE) FROM THE ROVNO AND BALTIC AMBERS - Zhantiev R.D. (My University, 2006)
Fossil beetles of the family Dermestidae are reviewed. Three new species are described: Dermestes progenitor and Megatoma electra from the Baltic amber and Dermestes vetustus from the Rovno amber (Late Eocene).
Keywords: Eocene; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен